Molecular subtype distribution of Cryptococcus neoformans in four areas of the United States. Cryptococcal Disease Active Surveillance Group. - Brandt, M E (1996)
To improve understanding of the epidemiology of cryptococcal disease, we analyzed the multilocus genotype distribution of 358 Cryptococcus neoformans isolates obtained from 251 patients through active surveillance in four U.S. geographic areas from 1992 through 1994. Isolates of the predominant enzyme electrophoretic type (ET), ET-1, were recovered in significantly greater proportion from Atlanta, Ga., Houston, Tex., and all major metropolitan areas of Alabama than from San Francisco, Calif. ET-2 and ET-7 complex (serotype AD) isolates were recovered predominantly from San Francisco. ET-3 was recovered less frequently from San Francisco than from the three other locations. These findings may reflect geographic differences in exposure to environmental strains or the identification of previously unrecognized C. neoformans clusters. Analysis by random amplified polymorphic DNA-PCR subtyping further divided 67 ET-1 isolates into 19 additional subtypes, none of which could be associated with a particular geographic region. Multiple isolates from the same patient always revealed the same multilocus enzyme electrophoresis and random amplified polymorphic DNA subtypes. No differences in subtype distribution were found when isolates from AIDS patients were compared with those from persons without or with another underlying disease, although one C. noeformans var. gattii isolate was obtained from an AIDS patient. When body site distribution was analyzed, ET-4 was disproportionately recovered from skin or surface body sites. Evidence for linkage disequilibrium in this fungal population suggests that virulent C. neoformans possesses a clonal population structure. Continued application of molecular subtyping methods will be useful in tracking the source, transmission, and relative virulence of different C. neoformans strains.